Protecting healthcare professionals from exhaustion: Personal belief in a just world as a personal and a coping resource - Correia, I.; Carvalho, H. (Personality and Individual Differences, 2025)
The present study examined for the first time the possibility that personal Belief in a Just World (BJW) is a personal resource for healthcare professionals, irrespective of the demands they face in their everyday work life, and/or a coping resource for facing demands due to the higher perceived suffering of their patients. A total of 497 healthcare professionals (physicians and nurses) voluntarily consented to answer an anonymous online survey. Self-reported measures of personal BJW, of the perception of patients' suffering, and of healthcare professionals' exhaustion were collected. We found a positive association between the perception of patients' suffering and healthcare workers' exhaustion, and a negative association between personal BJW and healthcare workers' exhaustion. Furthermore, a significant interaction between personal BJW and the perception of suffering on exhaustion showed that at lower levels of personal BJW, the higher the perception of patients' suffering the higher the exhaustion. In contrast, at higher levels of personal BJW the perception of patients' suffering was not associated with exhaustion. Our results supported the hypotheses of personal BJW operating both as a personal resource and a coping resource for healthcare professionals, underscoring the relevance of promoting workplace conditions that healthcare workers experience as just.